2000
DOI: 10.1021/ma9910437
|View full text |Cite
|
Sign up to set email alerts
|

Submicron Multiphoton Free-Form Fabrication of Proteins and Polymers:  Studies of Reaction Efficiencies and Applications in Sustained Release

Abstract: Nonlinear multiphoton photo-cross-linking and photopolymerization of proteins and polymers in solution have been used to direct the three-dimensional assembly of micron scale objects. Two aspects of fabricated proteinatious matrixes are examined in this paper: the efficiency of protein photopolymerization and the application of fabricated matrixes as sustained release devices. The efficiency of photoactivated cross-linking of the proteins bovine serum albumin and fibrinogen, using rose bengal, have been determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
178
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(186 citation statements)
references
References 27 publications
4
178
1
3
Order By: Relevance
“…We and others have shown that direct-write protein matrices can retain ligand-binding and catalytic functionality similar to that of their component proteins (23)(24)(25)(26)(27), implying that native electrostatic and hydrophobic interactions governing protein conformation remain significantly intact within microstructures. However, at pH extremes, unfavorable electrostatic interactions can disrupt the native state and result in protein unfolding (31,32).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We and others have shown that direct-write protein matrices can retain ligand-binding and catalytic functionality similar to that of their component proteins (23)(24)(25)(26)(27), implying that native electrostatic and hydrophobic interactions governing protein conformation remain significantly intact within microstructures. However, at pH extremes, unfavorable electrostatic interactions can disrupt the native state and result in protein unfolding (31,32).…”
Section: Resultsmentioning
confidence: 94%
“…High concentrations of protein in solution facilitate fabrication of robust microstructures. However, fabrication can be accomplished using protein solutions at concentrations as low as Ϸ1-10 ng/ml (27). Although some proteins undergo multiphoton crosslinking more efficiently than others, a broad range of proteins can be used (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MPP was first developed by Strickler and Webb, [62] and has now been used to create a range of high-resolution 3D free-form structures, including microchannels, [63][64][65] cantilevers, [66][67][68] microgears, [69,70] sub-micrometer oscillators, [71] hydrophobic atomic force microscopy tips, [72] and PhCs. [59,67,[73][74][75][76][77][78][79][80][81] Briefly, MPP utilizes the nonlinear nature of the multiphoton excitation process to only excite dye molecules in a very small volume around the focal point, with dimensions on the order of the resolution limit.…”
Section: Direct Writingmentioning
confidence: 99%
“…Hence, the starting materials limit the range of biological responses that can be obtained in the final product. Nonlinear multiphoton crosslinking and polymerization of proteins and monomers (e.g., alkaline phosphatase and acrylamide) can be achieved using femtosecond laser systems and such [6] processes have been successfully exploited for fabrication of 3D sustained-release devices on the subcellular biological scale by microstereolithography. [7] However, the small size (ca.…”
mentioning
confidence: 99%